2008
DOI: 10.1002/eej.20752
|View full text |Cite
|
Sign up to set email alerts
|

Service restoration problem in distribution power system using improved GA

Abstract: SUMMARYThe service restoration problem in distribution power systems has already been addressed with regard to this issue, for purposes such as the minimization of unrecovered load and power supply loss, considerations of priority sections, and preparation of switching procedures. However, since this involves the application of a number of methods, the related algorithms are complex. In this paper, in order to resolve this issue we first apply GA as an optimization method for investigation purposes, to simplif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…We demonstrated that the previous GA allows more efficient minimization of unrestored loads than previous methods [10]. However, detailed analysis shows that blackout sections remain around the branch points in most solutions.…”
Section: Proposed Methodsmentioning
confidence: 82%
See 3 more Smart Citations
“…We demonstrated that the previous GA allows more efficient minimization of unrestored loads than previous methods [10]. However, detailed analysis shows that blackout sections remain around the branch points in most solutions.…”
Section: Proposed Methodsmentioning
confidence: 82%
“…Thus, we analyzed the GA proposed in Ref. 10 and found that many faulty sections remain at branch points. In order to eliminate this deficiency, we tried to improve the GA in terms of mutation.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some of the studies investigate the restoration of the distribution system. In [15], by using the genetic algorithm (GA), the switching operation is minimized during the restoration process. It also reduces the required calculations time.…”
Section: Literature Reviewmentioning
confidence: 99%